IbM Pelatihan Pembuatan “Kerja Mas” (Keripik Jagung Manis) Berbasis Agropreneur - Muhammad Arief Rizka; Sri Nopita Primawati; Saidil Mursali (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
Technology and science for community (IbM) program aimed to create opportunities becameagropreneur (entrepreneurship based on processing agricultural products) for unemployment female throughimplementing training in making “Kerja Mas” (Keripik Jagung Manis) whose product had economic value andcould be marketed to general public. In implementing IbM program had been effort to improve knowledge andskills for female in Sesela Village in order to be able to develop business center of processing sweet cornwhich was affordable and could be received by public. This IbM program has implemented well throughsocialization activities, preparation activities, counseling material, training making Kerja Mas (keripik jagungmas), and mentoring. The result of implementing IbM program such as;(1) overall participants could make“kerja mas” product which already tested through organoleptic test, (2) “kerja mas” product had obtainedlicense of Dinkes P-IRT to guarantee decent healthy food consumption for public; (3) the product packing of“kerja mas” was fascinating and could be marketed in public; (4) establishing Joint Business Group (KUBE)“kerja mas” wa legal as center of processing sweet corn and as effort consummate agropreneur at Seselavillage, and (5) the result of IbM program could be published in Jurnal Ilmiah ISSN.